Moving beyond a tale of two genes: Strides in management of metastatic gastrointestinal stromal tumors and their supportive care - Clement Chung; Anthony Albayeh (American Journal of Health-System Pharmacy, 2026)
Abstract Purpose This article evaluates and summarizes key therapeutic advances and supportive care considerations for metastatic gastrointestinal stromal tumors (GISTs). Summary GISTs comprise a highly aggressive, heterogeneous group of soft tissue sarcomas that span multiple anatomic origins. Following surgical resection, GISTs often recur locally or metastasize to the liver. Collectively, GISTs represent the first group of solid malignancies that was elucidated as a mutation-driven neoplasm more than 2 decades ago. The treatment landscape for GISTs shifted with the advent of kinase inhibitors (eg, imatinib and sunitinib) targeting the constitutive activation of the cognate receptor kinase encoded by the proto-oncogene KIT or PDGFRA, which enables tumor cells to proliferate in a ligand-independent manner. The critical relevance of these oncogenic signaling pathways and, most recently, the introduction of novel kinase inhibitors (eg, avapritinib) that target a common mutation (PDGFRA D842V) associated with primary resistance to imatinib, sunitinib, and regorafenib or development of secondary resistance (eg, to regorafenib or ripretinib) have refined the management of GISTs, including so-called “wild-type” GISTs. Although these results are promising, tumor heterogeneity and varied resistance mechanisms to kinase inhibitors across different tumor locations limit the efficacy of these therapies, highlighting the therapeutic need to develop novel therapies and the important role of supportive care in mitigating treatment-related adverse effects and prolonging life by minimizing treatment interruptions for a group of malignancies that are highly dependent on oncogenic signaling. Conclusion Studies of the genomic and epigenetic landscape of GISTs have contributed to an understanding of their key molecular features and subsequent therapeutic advances. Supportive care is vital in optimizing treatment outcomes with these novel therapies.